ANALISYS OF CALCULATION METHODOLOGY OF PETROL LOSSES FROM HORIZONTAL TANKS AS A RESULT OF EVAPORATION - Чернобаєва, Н. А.; Бойченко, С. В.; Лазорко, О. І. (Science-based technologies, 2013)
The negative impact of losses from evaporation results not only in reduction of fuel resources and, consequently, cost of products that are lost, but also in negative ecological effect on the environment. Development of modern calculation techniques, prediction and reduction of evaporation burst of light hydrocarbons in the air based on promising methods for monitoring and process control in operation is considered to be an urgent problem. The object of research supports the tendency of gasoline to evaporation under different operating conditions. The subject of study is calculation methodology of petrol losses caused by evaporation. Hypothesis proposed by the authors is that the loss amount of light hydrocarbons from reservoirs depends on a set of factors affecting the tank and gasoline. The solution to establish the relationship between the current factors occurring during evaporation of light hydrocarbons from gasoline during manufacturing operations is viewed as an actual scientific problem.